Pelatihan Pendampingan Pastoral Usia Lanjut Bagi Asisten Imam di Paroki Santo Yohanes Pemandi Keuskupan Malang - Yohanes Subasno; Rosalia Wiwin; Fabianus Selatang; Martinus Irwan Yulius (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
Elderly Catholics in Santo Yohanes Pemandi Parish of Malang Diocese are no longer able to celebrate Weekly Mass in church due to their physical limitations. As lay people, the elderly have the right to receive pastoral guidance to confirm their faith in their old age. The number of priest is only one person and serves more than 1500 parishioners, it is not possible for priest to provide pastoral guidance to one elderly person by one. Assistant priest is appointed by the Bishop of Malang Diocese to assist priestly duties in the Parish. Assistant priests have limited knowledge and skills to provide pastoral care to the elderly. A model of pastoral assistance and training is needed for them to be able to assist the priest's duties in pastoral guidance for the elderly. The pastoral guidance model is developed and assessed by competent validators. The training was conducted five times, each lasting 90 minutes on the Sunday after mass. The training model pattern includes material delivery, question and answer, discussion, conclusions, and role playing. Testimonials from assistant priests stated that the training they participated in enabled them to carry out pastoral guidance for elderly Catholics in their work areas.